Association between Helicobacter pylori infection and kidney damage in patients with peptic ulcer. (1st January 2019) - Pan, Wei; Zhang, Hui; Wang, Li; Zhu, Tingting; Chen, Bo; Fan, Junming
Abstract: Background: Helicobacter pylori ( H. pylori ) is relevant to several renal diseases. Our previous research indicates that cytotoxin-associated gene A (CagA) of H. pylori increases secretion of serum immunoglobulin A1 (IgA1) and induces the underglycosylation of IgA1, one of the key factors causing IgA nephropathy. Here, we aimed to study the correlation between H. pylori infection and kidney damage in patients with peptic ulcer, and evaluate the effect of H. pylori eradication on kidney damage. Methods: 14 C-urea breath test and rapid urease tests were applied to H. pylori infection detection. Random urine samples are subjected to the albumin–creatinine ratio (ACR) examination. The correlation between ACR and H. pylori infection was analyzed in patients with peptic ulcer and healthy controls. The levels of IgA and underglycosylated IgA1 in serum are also detected by enzyme-linked immunosorbent assay (ELISA) and Helix aspersa lectin (HAA) binding assay. Results: (1) H. pylori infection rate in patients with peptic ulcer (88.14%) is significantly higher than that in healthy controls (42.68%). (2) There is a positive correlation between H. pylori infection and ACR abnormal in patients with peptic ulcer ( p  = .025), while showing a negative correlation in healthy individuals ( p  = .571). (3) Urinary ACR was uncorrelated with the severity of H. pylori infection in the 27 abnormal urinary ACR cases of the patients with peptic ulcer. (4) After H. pylori eradication, the ACR rates of H. pylori -positive patients with peptic ulcer were significantly decreased ( p <.01). Conclusions: (1) For the H. pylori- positive patients with peptic ulcer, H. pylori infection may be a risk factor resulting in kidney damage. (2) H. pylori eradication probably benefits to kidney damage relief and chronic kidney disease prevention.